Pelatihan Implementasi Perencanaan Keuangan Terhadap Efektivitas Pengelolaan Keuangan - Hendri Gunawan; Vega Anismadiyah; Vidya Amalia (Jurnal Abdimas Tri Dharma Manajemen, 2024)
Financial planning is an important aspect that must be implemented by everyone to achieve good financial conditions faster, so financial planning is needed. Financial planning is used as a strategy to achieve life goals. Careful financial management is very important to make our lives better now and in the future. Doing financial planning allows us to understand how each financial decision will affect other areas of the overall financial condition. When we look at our overall financial condition, we can develop both short-term and long-term impacts on life goals. We can more easily adapt to life changes and feel more confident with a healthy financial condition. Mentioned that we have strong financial quality and financially independent conditions in the future is a good intention to have. However, in realizing this dream, intention alone is enough. We must start to find and find the right way to manage finances. It should be realized that everyone’s way of managing finances will be different. But with the same goal, we can also take the essence or some tips and tricks in managing finances that can be adapted to our personality, needs, and lifestyle. Finding ways to manage finances that suit us needs to be done early. Since we were young and productive. Therefore, managing finances properly and healthily is needed so that our future can be well maintained and it will make it easier for us to meet all needs, whether planned or planned. We also need to pay attention to finding ways to manage finances from a young age, because finding ways or methods that suit things is easy. Keywords: financial planning, financial effectiveness